Does vancomycin trough concentration useful to predict optimal dosing during continuous venovenous haemofiltration? Preliminary findings from the valley study - Mohamad Nor, Fariz Safhan; Jamal, Janattul-Ain; Mohd Samat, Noryani; Ahmad, Mohd Kamil; Wan Ali, Wan Ahmad Syahril Rozli; Che Wan, Mohd Hafiz (Science Direct, 2017)
Introduction: Achieving optimal vancomycin dosing, particularly in septic critically ill patients receiving continuous renal replacement therapy (CRRT) is crucial. Established guidelines recommend the use of trough concentrations to manage vancomycin dosing in adult patients with gram-positive infections. Importantly, obtaining the area under the plasma concentration-time curve (AUC), based on the pharmacokinetic / pharmacodynamics (PK/PD) concept, is extremely required. Objective: This study aimed to describe the pharmacokinetics (PK) of vancomycin in Malaysian critically ill patients receiving CRRT, and the achievement of its therapeutic target, the ratio of the AUC to the minimum inhibitory concentration (MIC) of causative pathogen (AUC/ MIC >400), using a standard dosing regimen (750 mg 12 hourly). Methodology: This was a prospective PK study of vancomycin using standard dosing regimen, in critically ill patients receiving continuous venovenous haemofiltration (CVVH). Blood samples were collected at ten sampling times during a dosing interval. PK analyses were evalu- ated using non-compartmental method. Vancomycin trough concen- trations (15-20 mg/L), and the achievement of the ratio of AUC/ MIC>400, based on selected susceptibility breakpoint (MIC1⁄41 mg/L), were evaluated. Results: Fifty blood samples from five PK profiles of five patients were analysed. The median (interquartile range) of vancomycin total clear- ance (CLtotal) and volume of distribution (Vd) were 62.8 (45.1-62.7) mL/ min and 62.0 (48.7-94.2) L respectively, during CVVH. Maximum concentration, Cmax[30.8 (30.5-33.2) mg/L] was observed at 1.8`0.3 h. The standard dosing regimen (750 mg 12 hourly) resulted in AUC0-24 and Cmin of 400.1 (399.0-504.1) mg.h/L and 12.1 (10.7-16.1) mg/L, respectively. Of these, only two patients, who were anuric, obtained trough concentration between 15-20 mg/L and subsequently achieved the targeted AUC/MIC>400 (MIC1⁄41 mg/L). Conclusion: Obtaining trough concentration between 15-20 mg/L rela- tively achieved the desired AUC/MIC >400 for vancomycin during CVVH. Higher trough concentration (e.g 20-25 mg/L) may be required when targeting for a higher MIC (e.g >1mg/L). Initiation of a higher dosing regimen could also be necessary, particularly in patients undergoing CVVH with significant residual native renal function. Further data is required, from continuation of this study, to clarify the findings.